Infliximab: Pharmacological Properties, Mechanism of Action, and Clinical Applications in the Treatment of Selected Inflammatory Diseases - Słowik, Julia; Zapasek, Daniel; Bajak, Mateusz; Szczepański, Michał; Mamczur, Maciej; Kuliga, Marcin; Inglot, Julia; Inglot, Jadwiga; Feret, Dominik Maciej; Sowa, Damian (Quality in Sport, 2024)
Infliximab is a chimeric monoclonal antibody used in the treatment of chronic inflammatory diseases such as rheumatoid arthritis, Crohn’s disease, ulcerative colitis, and psoriasis. It functions by inhibiting tumor necrosis factor-alpha (TNF-α), a cytokine central to the inflammatory processes of these conditions. Since its approval in 1998, infliximab has significantly improved the management of patients who do not respond well to conventional therapies. The article provides a comprehensive review of infliximab’s pharmacological properties, its mechanism of action, FDA-approved uses, and its clinical benefits. It also discusses its safety profile, which includes potential risks like infections, infusion reactions, and long-term concerns such as an increased risk of malignancies. Regular monitoring of adverse effects is crucial for patient safety during treatment. Infliximab has demonstrated efficacy in reducing symptoms like pain, swelling, and skin lesions, and it helps in maintaining remission in conditions like Crohn’s disease and psoriasis. The drug is typically administered via intravenous infusion, and its dosing varies depending on the disease and patient response. Additionally, the article highlights the role of therapeutic drug monitoring (TDM) to optimize treatment outcomes and reduce healthcare costs. In conclusion, infliximab remains an essential therapeutic option for managing severe chronic inflammatory diseases, though its use requires careful monitoring due to potential risks. Ongoing research is expected to refine its use and expand its indications, further enhancing its clinical application in inflammatory disease management.